Genetics as a molecular window into recovery, its treatment, and stress responses after stroke. Issue 5 (4th April 2016) - Juth, Vanessa; Holman, E Alison; Chan, Michelle K; Cramer, Steven C
Abstract : Stroke remains a major source of adult disability in the USA and worldwide. Most patients show some recovery during the weeks to months following a stroke, but this is generally incomplete. An emerging branch of therapeutics targets the processes underlying this behavioral recovery from stroke toward the goal of reducing long-term disability. A key factor hampering these efforts is the very large degree of variability between stroke survivors. Available data suggest that genetic differences could explain an important fraction of the differences between subjects. The current review considers this from several angles, including genetic differences in relation to drugs that promote recovery. Genetic factors related to physiological and psychological stress responses may also be critically important to understanding recovery after stroke and its treatment. The studies reviewed provide insights into recovery and suggest directions for further research to improve clinical decision-making in this setting. Genetic differences between patients might be used to help clinical trials select specific patient subgroups, on a biological basis, in order to sharpen the precision with which new treatments are evaluated. Pharmacogenomic factors might also provide insights into inter-subject differences in treatment side effects for pharmacological prescriptions, and behavioral interventions, and others. These efforts must be conducted with the strictest ethical standards given the highly sensitive nature of genetic data. Understanding the effect of selected genetic measures could improve a clinician's ability to predict the risk and efficacy of a restorative therapy and to make maximally informed decisions, and in so doing, facilitate individual patient care.